The third world in the global 1960s (Protest, culture and society, volume 8) - Christiansen, Samantha; Scarlett, Zachary A (Protest, culture and society, 2012)
Decades after the massive student protest movements that consumed much of the world, the 1960s remain a significant subject of scholarly inquiry. While important work has been done regarding radical activism in the United States and Western Europe, events in what is today known as the Global South-Asia, Africa, and Latin America-have yet to receive the requisite attention they deserve. This volume inserts the Third World into the study of the 1960s by examining the local and international articulations of youth protest in various geographical, social, and cultural arenas. Rejecting the notion that the Third World existed on the periphery, it situates the events of the 1960s in a more inclusive context, building a richer, more nuanced understanding of the Global 1960s that better reflects the dynamism of the period.